Ethyl 2-(4-bromophenyl)-1-[3-(1H-imidazol-1-yl)propyl]-1H-benzimidazole-5-carboxylate monohydrate - Yoon, Yeong Keng (International Union of Crystallography, 2011)
In the title compound, C(22)H(21)BrN(4)O(2)·H(2)O, the two pyrazole rings are essentially planar [maximum deviations 0.002 (1) and 0.002 (1) Å], and form a dihedral angle of 73.46 (9)°. The dihedral angle between the benzene rings is 29.33 (7)°. In the crystal, molecules are connected via C—H⋯O and O—H⋯N hydrogen bonds, forming layers in the ab plane.